A crosssectional study to explore the mediating effect of intrinsic aspiration on the association between unconditional positive self-regard and posttraumatic growth - Murphy, David; Demetriou, Evangelia; Joseph, Stephen (Routledge, 2015)
Person-centered psychotherapy is based on the growth paradigm of psychological distress. Person-centered therapy is, therefore, ideally placed to facilitate posttraumatic growth. There were two aims of this study. The first was to explore the association between unconditional positive self-regard and the construct of posttraumatic growth. The second was to explore the mediating effect of intrinsic aspirations on the association between unconditional positive self-regard and posttraumatic growth. A crosssectional correlation design was used to ask a sample of Cypriot origin participants (N = 99) to complete the Unconditional Positive Self-Regard Scale (UPSR), Intrinsic Aspirations subscale of the Aspirations Index and Post Traumatic Growth Inventory (PTGI). Findings showed that unconditional positive self-regard was significantly positively correlated with posttraumatic growth and that the association between unconditional positive self-regard and posttraumatic growth was successfully partially mediated by intrinsic aspirations. This is the first study to test for the mechanisms by which unconditional positive self-regard predicts posttraumatic growth. The findings also support a link between the phenomenon of posttraumatic growth and personcentered theory at a construct level. Implications for person-centered therapy are discussed and suggestions for further research are proposed.